Pathology at a glance - Finlayson, Caroline J.; Newell, Barry A. T. (The at a glance series, 2009)
This title provides key information on the occurrence, mechanistic cause and clinical appearance of the major diseases students need to understand. It is divided into three sections, covering general, systematic and multi-system pathology.